2009
DOI: 10.1007/s10342-009-0287-1
|View full text |Cite
|
Sign up to set email alerts
|

Plastid DNA variation in Prunus serotina var. serotina (Rosaceae), a North American tree invading Europe

Abstract: Black cherry (Prunus serotina) is a tree from North America, where it is often used for economical purposes, whereas it is widespread and invasive in Europe. Plastid DNA variation was Wrst investigated in both its native and invasive ranges using microsatellite loci and sequences of three intergenic spacers (trnT-trnL, trnD-trnT and trnS-trnG). This analysis was focused on P. serotina var. serotina, with the inclusion of samples of closely related taxa. Length variation at a microsatellite locus (ccmp5) and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
1
7
0
2
Order By: Relevance
“…They found that cpDNA of the F1 generation was inherited maternally and fi rst proved that the cpDNA in conifers is of maternal inheritance. Our results also confi rm the high variability of chloroplast non-coding regions, especially in trnL-trnF sequences, which is suitable for distinguishing species with close genetic relationships (Taberlet et al, 1991;Chen et al, 2002;Petitpierre et al, 2009). …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…They found that cpDNA of the F1 generation was inherited maternally and fi rst proved that the cpDNA in conifers is of maternal inheritance. Our results also confi rm the high variability of chloroplast non-coding regions, especially in trnL-trnF sequences, which is suitable for distinguishing species with close genetic relationships (Taberlet et al, 1991;Chen et al, 2002;Petitpierre et al, 2009). …”
Section: Discussionsupporting
confidence: 79%
“…For the restriction enzyme digestion, we referred to Qi et al (1999), Rajora and Dancik (1992), Hela et al (2004) and Petitpierre et al (2009). The amplifi ed fragments of 12 primers were digested by fi ve restrictive endonucleases, i.e., AluI, EcoRI, HinfI, HindIII and TaqI, and retained overnight at the optimum reaction temperature of each enzyme.…”
Section: Restriction Enzyme Analysismentioning
confidence: 99%
“…[16] constructed phylogenetic trees based on separate data sets using the sequence of ITS and trn L- trn F, but they were not statistically congruent, which indicates that the 13 Morus species were of non-monophyletic origin. The sequence variations of the other intergenic regions in the chloroplast genome could provide genetic information for phylogenetic analyses as well, as reported in Prunus serotina [25] and Elymus caninus [26] etc. In this study, 10 cpDNA non-coding regions, accounting for 17.1 kb (about 10.79% of the chloroplast genome) were specifically amplified and 70 primer–enzyme combinations were used in an attempt to detect interspecies and intra-species polymorphism.…”
Section: Resultsmentioning
confidence: 98%
“…could also be used for P. serotina, a conclusion seconded with experimentation by Wünsch and Hormaza (2007). The use of P. serotina, Q. robur, and Q. petraea cpDNA has shown that significant diversity can be seen even in the presence of low sequence polymorphisms (Petit et al 2002;Petitpierre et al 2009).…”
Section: Marker Technologies In Conservation and Tree Improvementmentioning
confidence: 97%